2019
DOI: 10.1016/j.celrep.2019.11.085
|View full text |Cite
|
Sign up to set email alerts
|

miRNA551b-3p Activates an Oncostatin Signaling Module for the Progression of Triple-Negative Breast Cancer

Abstract: Highlights d miR551b-3p translocates to the nucleus and activates STAT3 transcription d Importin-8 (IPO8) is required for the nuclear translocation of miR551b-3p d miR551b-3p activates the expression of OSM family genes for autocrine signaling loop d Inhibition of miR551b-3p disrupts OSM-mediated signaling addiction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 59 publications
2
61
0
Order By: Relevance
“…These data indicate that the DAT/SLC6A3 is often genetically amplified in many types of cancers and involved in poor prognosis and that it is therefore sensibly targetable by DAT inhibitors such as Benz. It has been shown that STAT3 was able to activate the autocrine feedforward loop by inducing oncostatin M, oncostatin M receptor (OSMR), IL-31, IL-31 receptor, and gp130 [glycoprotein 130, also called IL-6 signal transducer (IL6ST), IL6Rβ, oncostatin M receptor subunit α] [31]. Next, we therefore searched to determine whether the expression of STAT3 and DAT/SLC6A3 were correlated with the expression of other genes related to the STAT and NF-κB signals in colorectal adenocarcinoma patient-derived samples (594 cases).…”
Section: Clinical Significance Of Dat and Statmentioning
confidence: 99%
“…These data indicate that the DAT/SLC6A3 is often genetically amplified in many types of cancers and involved in poor prognosis and that it is therefore sensibly targetable by DAT inhibitors such as Benz. It has been shown that STAT3 was able to activate the autocrine feedforward loop by inducing oncostatin M, oncostatin M receptor (OSMR), IL-31, IL-31 receptor, and gp130 [glycoprotein 130, also called IL-6 signal transducer (IL6ST), IL6Rβ, oncostatin M receptor subunit α] [31]. Next, we therefore searched to determine whether the expression of STAT3 and DAT/SLC6A3 were correlated with the expression of other genes related to the STAT and NF-κB signals in colorectal adenocarcinoma patient-derived samples (594 cases).…”
Section: Clinical Significance Of Dat and Statmentioning
confidence: 99%
“…MicroRNA plays a broad range of oncogenic functions in TNBC including cell proliferation, apoptosis, migration, metastasis, epithelial mesenchymal transition (EMT) process, and angiogenesis 14 . For example, miR551b-3p is aberrantly expressed in TNBC and targeting miR-551b with anti-miR551b-3p reduces tumor growth and metastasis 15 . Additionally, miR-221 transfer from TNBC cells via microvesicles induces EMT and promotes the malignant potential of recipient cells 16 .…”
Section: Introductionmentioning
confidence: 99%
“…is often genetically amplified in many types of cancers and involved in poor prognosis and therefore sensibly targetable by DAT inhibitors such as Benz. It has been shown that STAT3 was able to activate the autocrine feedforward loop by inducing oncostatin M, oncostatin M receptor (OSMR), IL-31, IL-31 receptor, and gp130 [glycoprotein 130, also called IL-6 signal transducer (IL6ST), IL6Rβ, oncostatin M receptor subunit α] [26]. We therefore next searched to determine whether the expression of STAT3 and DAT/SLC6A3 were correlated with the expression of other genes related to the STAT and NF-κB signals in colorectal adenocarcinoma patient-derived samples (594 cases).…”
Section: Clinical Significance Of Dat and Statmentioning
confidence: 99%